Almost complete absence of the scalp and body hair in association with oligodontia and zygodactylous palmar triradii - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2001)
We describe an 18-year-old girl with a distinctive facial appearance, almost complete absence of the scalp and body hair, absence of the eyebrows and eyelashes, oligodontia, conically shaped maxillary central incisors and zygodactylous palmar triradii suggesting for syndactyly type I. Clin Dysmorphol 10: 269-272 (C) 2001 Lippincott Williams & Wilkins.
Keywords: ectodermal dysplasia; hypotrichosis; oligodontia; conically shaped maxillary central incisors; zygodactylous palmar triradii